Vitamin D, Calcium, Alkaline Phosphatase, and Parathyroid Hormone in Patients with and without Chronic Periodontitis - Pradhan, Shaili; Agrawal, Shweta; Shrestha, Benju (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Introduction: Periodontal diseases comprise a group of inflammatory diseases caused by bacteria that colonise the tooth surface and infect surrounding soft tissues, ultimately leading to tooth loss. Vitamin D, calcium, alkaline phosphatase, and parathyroid hormone have role in bone metabolism both in health or in disease. Objective: To compare serum Vitamin D, calcium, alkaline phosphatase, and parathyroid hormone levels in patients with generalised chronic periodontitis and healthy periodontium. Methods: A cross-sectional analytical study was done in 80 patients visiting Department of Dental Surgery from July to December 2019. Clinical parameters measured were plaque index, gingival index, clinical attachment level, and pocket depth in the healthy periodontium and generalised chronic periodontitis. Blood investigation for serum Vitamin D, calcium, alkaline phosphatase (ALP), and parathyroid hormone (PTH) level were done. Data was analysed in SPSS v.16. Results: Out of total 80 patients enrolled (mean age of 36.20±7.37 years), 40 (50%) patients had healthy periodontium and 40 (50%) had generalised chronic periodontitis. Mean levels of serum Vitamin D (P=0.006) and calcium (P=0.020) were significantly higher in chronic periodontitis patient compared to healthy controls while no significant intergroup differences were seen with respect to ALP (P=0.267) and PTH (P=0.351). Conclusion: No significant differences were found in the levels of ALP and PTH between generalised chronic periodontitis and healthy patients and higher levels of Vitamin D and calcium were seen in generalised chronic periodontitis patients as compared to healthy patients.